The crops of bean and maize under dry land conditions in the state of Zacatecas, Mexico from 1980 to 2008 - Luna Flores, Maximino; Hernández Martínez José; Luna Estrada, Maximino Gerardo; Zelaya de Santiago, Luis Humberto; García Hernández Serafín (Revista Mexicana de Ciencias Agrícolas, 2018)
The bean and maize grain crops have been the most important, agriculturally, socially and economically in the State of Zacatecas, for many years. The main objectives of this work were to see if the surfaces planted and damaged, and if the production and the unit yields of beans and grain maize planted under dry land conditions in the State of Zacatecas, have varied from 1980 to 2008; and to evaluate how rainfall affects these variables. Data published by SAGARPA on the Internet was used. Correlations and regressions between the data for variables of each crop were obtained for further accuracy in the analysis. Rainfall during the crop season and its distribution was found to affect considerably the sown and damaged areas, unit yield and the production volume of beans and dry land corn. The damaged surface of dry land bean (15.2%) was lower than that of maize (18.6%); the surface for beans increased by 543 ha per millimeter less of rainfall and precipitation and, for maize, in 256 h. Average yield for dry land beans increased 1.62% per year, and for maize, this figure was 1.46%. The surface planted with beans dropped significantly in recent years due to the productive reconversion program, which increased mostly the surfaces of fodder oats and maize.